Surface Roughness of Denture Base Acrylic Resins After Processing and After Polishing - Julie C. Berger, DDS, MS;1 Carl F. Driscoll, DMD;2 Elaine Romberg, PhD;3 (Journal of Prosthodontics, 2006)
Circumstances exist in which the need to adjust denture base acrylic resins is necessary.